Ex Vivo Effect of Novel Lipophosphonoxins on Root Canal Biofilm Produced by Enterococcus faecalis: Pilot Study - Morozova, Yuliya; Voborná, Iva; Žižka, Radovan; Bogdanová, Kateřina; Večeřová, Renata; Rejman, Dominik; Kolář, Milan; Do Pham, Duy Dinh; Holík, Pavel; Moštěk, Roman; Rosa, Matej; Pospíšilová, Lenka (Life, 2022)
(1) Background: The root canal system has complex anatomical and histological features that make it impossible to completely remove all bacteria by mechanical means only; they must be supplemented with disinfectant irrigation. Current disinfectants are unable to eliminate certain microorganisms that persist in the root canal, resulting in treatment failure. At the Institute of Organic Chemistry and Biochemistry, Prague, novel substances with the bactericidal effect, termed lipophosphonoxins (LPPOs), have been discovered. The aim of this pilot study was to investigate the ex vivo effects of second- and third-generation LPPOs on Enterococcus faecalis and compare them with 5% sodium hypochlorite (NaOCl), 0.12% chlorhexidine digluconate, and 17% ethylenediaminetetraacetic acid (EDTA). (2) Methods: The root canal's dentin was used as a carrier for biofilm formation in the extracted human mature mandibular premolars. The samples were filled with cultivation broth and 0.25% glucose with tested solutions. In control samples, only fresh cultivation broth (negative control) and cultivation broth with bacterial suspension (growth control) were used. Each sample was inoculated with E. faecalis CCM4224 except for the negative control, and cultivation was performed. To determine the number of planktonic cells, the sample content was inoculated on blood agar. To evaluate biofilm formation inhibition, samples were placed in tubes with BHI. (3) Results: LPPOs exhibited a reduction in biofilm growth and bacteria comparable to NaOCl, and they were superior to other tested disinfectants. (4) Conclusions: The study results suggest the effect of lipophosphonoxins on E. faecalis CCM 4224 reduces planktonic bacterial cells and inhibits formation of biofilm in root canal samples.